Evaluasi Pelaksanaan Program Deteksi Dini Kanker Serviks dengan Metode Inspeksi Visual Asam Asetat (IVA) dan Deteksi Dini Kanker Payudara dengan Metode Clinical Breast Examination (CBE) - Rizky Amelia; Ulva Nurul Fajriyah; Dhita Aulia Octaviani (JURNAL KEBIDANAN, 2019)
Cancer is the number two cause of death in the world. 10 types of cancer in Indonesia, breast cancer ranks first (21.69%) followed by cervical cancer (17%). To prevent the disease, The Government launched an early detection program of cervical cancer with Visual Acetic Acid Inspection Method and early detection of breast cancer by Clinical Breast Examination. The region of Central Java especially Semarang Regency from 159.621 women of childbearing age only 771 (0.44%) examined. Therefore need to be evaluated as measured on the basis of indicators of inputs, process, outputs.The researche aims to evaluated the implementation of early detection program of cervical cancer with Visual Acetic Acid Inspection Method and early detection of breast cancer with Clinical Breast Examination Method at Public Health Centreworking areas of  Semarang Regency. This research was evaluated of the program, namely the formative evaluation. The research design used descriptive analytics using Mixed Method Sequential Explanatory which there Sequential Mixed Method. The results of this research showed that from the input components, that was 100% of Health Centreworking areas of  Semarang Regency has excellent value. On the process components rated 88.5% very good, 11.5% good. On the component Output there were 15.4% Public Health Centre very good, 7.7% good, 26.9% enough, 46.2% less, and 3.8% very less.The research  concluded was that inputs of the programs that rated very good not necessarily produce outputs very good as well, it was influenced by the rated of process. Therefore, suggestions for the implementation of the program in order to further improve the socialization and advocated, the implementation was done more regularly so that the motivation of the people will be increase, and than  conducting periodic monitoring.